Dhammapada vatthu : Dhammapadaaṭṭhakathā Mranʻ mā pranʻ - Buddhaghosa (Praññʻ thoṅʻ cu Mranʻ mā Nuiṅʻ ṅaṃ toʻ ʼA cuiʺ ra, Sāsanā reʺ Vanʻ krīʺ Ṭhāna, Sāsanā reʹ Ūʺ cīʺ Ṭhāna Puṃ nhipʻ Tuikʻ n* ruikʻ nhipʻ saññʻ, 1992)
Burmese translation of Buddhaghosa's Dhammapadaṭṭhakathā, classical commentary on Dhammapada, Buddhist canonical text.